Lingkup Penelitian Kualitatif dan Alternatif Penggunaannya dalam Pengembangan llmu di Fakultas Ekonomi - Sentosa, Purbayu Budi (JURNAL BISNIS STRATEGI, 2006)
Quantitative research is commonly used within positivism paradigm whereas qualitative one is a part of naturalistic paradigm. However, positivism paradigm has been ctritizied because of simplicity of problems. Reseach method used in qualitative research are multi methodologies, so that thereÂ  is no specific methodology. Intact, there is no superior or inferior methods that can be used in qualitative research.Â  Eventhough, quantitative and qualitative research are developed within different paradigm both reseach have similarity in regard to the need for keeping validity of reseach.Qualitative research can be used as an alternative of quantitative research tor students and lecturers in doing economic research.